2020
DOI: 10.1101/2020.07.09.20149997
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological state and family functioning of University of Ibadan students during the COVID-19 lockdown

Abstract: Background: The curtailment of social gatherings as well as lack of online academic engagement, due to the COVID-19 lockdown, could have potentially damaging effects on the psychological state of university students in Nigeria. This study examined the prevalence of anxiety and depression, including associated factors and coping methods among undergraduate students in a Nigerian university. It also examined the association between psychological state and family functioning. Methods: The study design was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
4
16
0
Order By: Relevance
“…Those study subjects from the non-health area of study were more anxious in this survey. This is in line with previous studies [16][17][18]. Students in the health and health-related field are expected to have more appropriate and accurate information and may help them to get prepared easily to protect themselves from the pandemic which in turn will help to reduce anxiety due to the adverse condition.…”
Section: Plos Onesupporting
confidence: 88%
See 1 more Smart Citation
“…Those study subjects from the non-health area of study were more anxious in this survey. This is in line with previous studies [16][17][18]. Students in the health and health-related field are expected to have more appropriate and accurate information and may help them to get prepared easily to protect themselves from the pandemic which in turn will help to reduce anxiety due to the adverse condition.…”
Section: Plos Onesupporting
confidence: 88%
“…Previous studies revealed that internet access [16][17][18], self-efficacy [19][20][21], self-rated health [9], age, marital status, and sex of the students were significantly associated with depression [22]. Similarly, age [15,[22][23][24][25][26][27][28][29][30][31][32], year of study, and social support [15], marital status, and sex of the students were significantly associated with anxiety [15,22].…”
Section: Introductionmentioning
confidence: 98%
“…This also seems to have been the case in other countries. For instance, a rate of 31.9% was found in Nigerian students during their lockdown (Ojewale, 2020), whereas the pre-COVID rate was 12.7% (Seun-Fadipe & Mosaku, 2017). Concerning anxiety, our results showed that during lockdown, 33.38% of our participants had probable anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…One study in Nigeria indicated that the prevalence of anxiety and depression was 31.9% and 41.4% respectively. 13 In Ethiopia, two studies reported that the prevalence of depression, anxiety, and stress was 21.2% and 77.2%, 27.7% and 71.8%, and 32.5% and 48.5% respectively. 14 , 15 Kinds of literature also indicated that age, sex, history of medical illness, living in a State/Region with a high incidence of COVID-19, family income, having family members infected with the disease, the practice of preventive measures, and residence were determinants of depression, anxiety, and stress.…”
Section: Introductionmentioning
confidence: 99%